2015
DOI: 10.1039/c5ra10318e
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and charge carrier dynamics in Dy substituted phase stabilized cubic Bi2O3

Abstract: Room temperature phase stabilization of cubic Bi 2 O 3 has been achieved by adding Dy 2 O 3 as dopant, using low temperature citrate-auto-ignition method. The samples were sintered at different temperatures retaining the cubic fluorite structure. Rietveld refinement of the X-ray diffraction profiles has given the detailed microstructural information of the prepared samples.The transmission electron micrographs confirmed the presence of atomic planes as obtained from X-ray diffraction. The Uv-Vis spectra show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As far as applications in energy conversion are concerned, such as chemical processing, controlled combustion, and sensing, solid electrolytes are the most important part of electrochemical devices. Recent investigations established that bismuth oxide-based compounds have emerged as one of the important materials in the family of solid electrolytes over conventional zirconia- or ceria-based electrolytes. According to literature review, out of six polymorphs of Bi 2 O 3 , the body-centered cubic (bcc) γ-phase, face-centered cubic (fcc) δ-phase, tetragonal β-phase, and monoclinic α-phase are the very important materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as applications in energy conversion are concerned, such as chemical processing, controlled combustion, and sensing, solid electrolytes are the most important part of electrochemical devices. Recent investigations established that bismuth oxide-based compounds have emerged as one of the important materials in the family of solid electrolytes over conventional zirconia- or ceria-based electrolytes. According to literature review, out of six polymorphs of Bi 2 O 3 , the body-centered cubic (bcc) γ-phase, face-centered cubic (fcc) δ-phase, tetragonal β-phase, and monoclinic α-phase are the very important materials.…”
Section: Introductionmentioning
confidence: 99%
“…Among different phases of bismuth oxide, 25% inherent vacancy of oxygen sublattice makes the δ-Bi 2 O 3 structure highly disordered and an excellent oxygen ion (O 2– ) conductor at elevated temperature [∼1 Ω –1 ·cm –1 at 750 °C] . This high temperature stable phase can be stabilized at room temperature on doping of the Bi 2 O 3 matrix with either isovalent (e.g., Dy 3+ , Ho 3+ , and Y 3+ ) , or aliovalent (e.g., Ba 2+ ) cations . However, such substitutions result in lowering of the ionic conductivity of doped Bi 2 O 3 systems due to ⟨111⟩ ordering of disordered oxygen sublattice .…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that EPDM with 40 and 50 vol.-% BaTiO 3 both have semicycles, which is called Cole–Cole semicycle. 32, 33 Each semicycle is ascribed to one Debye relaxation caused by the interfacial polarisation between BaTiO 3 and EPDM matrix. 34 It showed that at 40 vol.-% of BaTiO 3 , EPDM composite starts to show greater interfacial polarisation between BaTiO 3 and EPDM matrix.…”
Section: Resultsmentioning
confidence: 99%
“…In literatures, Cole-Cole model and Debye relaxation are oen used to evaluate the dielectric properties of compostes. [32][33][34][35][36] Cole-Cole semicycles are oen shown by the plot of dielectric constant versus dielectric loss. 29…”
Section: Effect Of Coupling Agents On Dielectric Propertiesmentioning
confidence: 99%